The Optimal Application of Medium Potency Topical Corticosteroids in Preventing Laser-Induced Inflammatory Responses—An Animal Study - Kuang-Ling Ou; Chia-Cheng Wen; Ching-Ya Lan; Yu-An Chen; Chih-Hsin Wang; Yi-Wen Wang (Life, 2021)
Background: During ablative fractional resurfacing (AFR) laser therapy, thermal damage to the skin is inevitable, resulting in inflammatory responses and small wounds. Corticosteroids are known for their anti-inflammatory effect. However, inappropriate application of corticosteroids carries the risk of delayed wound healing. Therefore, we aimed to find the optimal administration route, timing, and duration of medium potency corticosteroid treatment to prevent AFR laser-induced inflammatory responses and to minimize the risk of delayed wound healing. Methods: We determined the anti-inflammatory efficacy of corticosteroids by skin erythema and tissue biopsies on C57BL/6 mice. Wound healing was evaluated by crust area and epithelial gap. Finally, Masson’s trichrome stain and α-SMA immunohistochemistry stain were used to analyze scar contracture. Results: Our results demonstrated that one dose of medium-potency topical corticosteroid applied immediately after AFR laser treatment could prevent erythema effectively with minimal disruption to wound healing. Notably, when more than one dose was administered, wound healing was delayed and scar contracture was aggravated by the application of medium-potency topical corticosteroids in a dosage-dependent manner. Conclusion: Our findings suggested that single-dose medium-potency topical corticosteroids could potentially improve AFR laser-induced acute inflammatory responses in clinical applications.